A stepwise approach for the management of bilateral chylothoraxes from cisterna chyli trauma - Vincent Phan; Syed H. Ali; Brady Olson; Raj Keriwala (Respiratory Medicine Case Reports)
Chylothorax is a rare complication characterized by chyle accumulation in the pleural space, leading to respiratory and nutritional deficits. We present a 53-year-old male who developed bilateral high-output chylothorax following radical nephrectomy and lymph node dissection for renal cell carcinoma. Despite conservative management with a fat-free diet, total parenteral nutrition, and octreotide, chyle output remained >1L/day. Lymphangiography identified thoracic duct leakage, but embolization and cisterna chyli fenestration were unsuccessful. The patient ultimately underwent video-assisted thoracoscopic surgery (VATS) with talc pleurodesis, resulting in resolution. This case highlights the importance of a multidisciplinary, stepwise approach in managing refractory chylothorax, with VATS and talc pleurodesis as effective interventions when conservative therapies fail.